The gilded age. The complete first season [videorecording (DVD)] - Coon, Carrie, 1981-; Spector, Morgan, 1980-; Jacobson, Louisa, 1991-; Benton, Denée; Farmiga, Taissa, 1994-; Richardson, Harry (Actor); Ritson, Blake; Cocquerel, Thomas, 1990-; Jones, Simon, 1950-; Gilpin, Jack, 1951-; Nixon, Cynthia; Baranski, Christine (2022)
A period of immense economic change, of huge fortunes made and lost, and the rise of disparity between old money and new. A wide-eyed young scion of a conservative family, Marian, embarks on a mission to infiltrate the wealthy neighboring clan or her aunts Agnes van Rhijn and Ada Brook, dominated by ruthless railroad tycoon George Russell, his rakish son, Larry, and his ambitious wife, Bertha. In this exciting new world that is on the brink of the modern age, will Marian follow the established rules of society, or forge her own path?